Enabling Clinical Technologies for Hyperpolarized 129Xenon Magnetic Resonance Imaging and Spectroscopy. (9th June 2021) - Khan, Alixander S.; Harvey, Rebecca L.; Birchall, Jonathan R.; Irwin, Robert K.; Nikolaou, Panayiotis; Schrank, Geoffry; Emami, Kiarash; Dummer, Andrew; Barlow, Michael J.; Goodson, Boyd M.; Chekmenev, Eduard Y.
Abstract: Hyperpolarization is a technique that can increase nuclear spin polarization with the corresponding gains in nuclear magnetic resonance (NMR) signals by 4–8 orders of magnitude. When this process is applied to biologically relevant samples, the hyperpolarized molecules can be used as exogenous magnetic resonance imaging (MRI) contrast agents. A technique called spin‐exchange optical pumping (SEOP) can be applied to hyperpolarize noble gases such as 129 Xe. Techniques based on hyperpolarized 129 Xe are poised to revolutionize clinical lung imaging, offering a non‐ionizing, high‐contrast alternative to computed tomography (CT) imaging and conventional proton MRI. Moreover, CT and conventional proton MRI report on lung tissue structure but provide little functional information. On the other hand, when a subject breathes hyperpolarized 129 Xe gas, functional lung images reporting on lung ventilation, perfusion and diffusion with 3D readout can be obtained in seconds. In this Review, the physics of SEOP is discussed and the different production modalities are explained in the context of their clinical application. We also briefly compare SEOP to other hyperpolarization methods and conclude this paper with the outlook for biomedical applications of hyperpolarized 129 Xe to lung imaging and beyond. Abstract : The use of hyperpolarized 129 Xe has the potential to revolutionize clinical imaging, offering a non‐ionizing contrast of organ function complementary to that of CT imaging and conventional MRI. In this Review, the physics of spin‐exchange optical pumping (SEOP) is discussed, production modalities of hyperpolarized 129 Xe are explained, and biomedical applications to lung imaging and beyond are described.